RHOAming Through the Nucleotide Excision Repair Pathway as a Mechanism of Cellular Response Against the Effects of UV Radiation - Magalhaes, Yuli T.; Silva, Gisele E. T.; Osaki, Juliana H.; Rocha, Clarissa R. R.; Forti, Fabio L. (Frontiers in Cell and Developmental Biology, 2020)
Typical Rho GTPases include the enzymes RhoA, Rac1 and Cdc42 that act as molecular switches to regulate essential cellular processes in eukaryotic cells such as actomyosin dynamics, cell cycle, adhesion, death and differentiation. Recently, it has been shown that different conditions modulate the activity of these enzymes, but their functions still need to be better understood. Here we examine the interplay between RhoA and the NER (Nucleotide Excision Repair) pathway in human cells exposed to UVA, UVB or UVC radiation. The results show high levels and accumulation of UV-induced DNA lesions (strand breaks and cyclobutane pyrimidine dimers, CPDs) in different cells with RhoA loss of function (LoF), either by stable overexpression of negative dominant RhoA (RhoA-N19 mutant), by inhibition with C3 toxin or by transient silencing with siRNA. Cells under RhoA LoF showed reduced levels of γH2AX, p-Chk1 (Ser345) and p-p53 (Ser15) that reflected causally in their accumulation in G1/S phases, in low survival rates and in reduced cell proliferation, also in accordance with the energy of applied UV light. Even NER-deficient cells (XPA, XPC) or DNA translesion synthesis (TLS)-deficient cells (XPV) showed substantial hypersensitivity to UV effects when previously submitted to RhoA LoF. In contrast, analyses of apoptosis, necrosis, autophagy and senescence revealed that all cells displaying normal levels of active RhoA (RhoA-GTP) are more resistant to UV-promoted cell death. This work reaffirms the role of RhoA protein signaling in protecting cells from damage caused by UV radiation and demonstrates relevant communicating mechanisms between actin cytoskeleton and genomic stability.